A Comprehensive Review of Free Radicals, Oxidative Stress, and Antioxidants: Overview, Clinical Applications, Global Perspectives, Future Directions, and Mechanisms of Antioxidant Activity of Flavonoid Compounds - Sefren Geiner Tumilaar; Ari Hardianto; Hirofumi Dohi; Dikdik Kurnia (Journal of Chemistry)
Absorption​ of free radicals in the body cannot be done by antioxidant compounds originating from the human body, so exogenous antioxidants are required to help in their natural antioxidant action. Oxidative stress can be caused by an imbalance of free radical inhibitors and the accumulation of free radicals that enter cellular structures. Synthetic antioxidants found in external antioxidants are not the primary choice because they are harmful and carcinogenic. Therefore, using natural ingredients provides a necessary alternative to constructing novel natural antioxidants. Recent studies have highlighted critical analysis and evaluation that flavonoids are a unique class of secondary metabolites found in plants and used in communities as traditional therapeutics with proven bioactivity. This could support new discoveries based on various herbal medicines and in addition, the functional effectiveness of flavonoids as antioxidants against free radicals. In this review, there are several strengths in the discussion. First, the study takes a comprehensive approach by covering various aspects, including the properties and sources of free radicals, oxidative stress in relation to different diseases, antioxidant defense mechanisms, and the specific antioxidant mechanisms of flavonoids. Second, the focus on natural antioxidants, especially flavonoids, and also discussion about clinical applications and human studies, limitations, global perspectives, and future research directions of flavonoids compounds become references in the selection of natural medicines. But, several constraints should be considered when interpreting the findings of this review. First, the discussion about the mechanism of antioxidant compounds is only discussed in general and only takes one example of a compound (flavonoid) that has the potential as an antioxidant. Second, the lack of findings regarding the relationship between several diseases discussed with free radicals. Third, a limited number of studies investigated regarding clinical applications and human studies of some of the diseases discussed.